INTENSIVE ONLINE TRAINING DURING THE COVID-19 PANDEMIC FOR INDONESIAN SCIENCE TEACHERS TO WRITE GOOD SCIENTIFIC ARTICLES - Sentot Kusairi; Nurul Hidayat; Heriyanto Heriyanto; Atsnaita Yasrina (Jurnal Pembelajaran Sains, 2020)
Writing works in the form of scientific articles is one of the skills that teachers must have. Not only for promotion needs, but mainly to contribute to academic society on research results in the realm of teaching. Scientific articles written by teachers will enrich an scientific documentations. Moreover when the topics raised in the scientific article are the actual representations of the conditions of teaching and learning in the classroom or school. If many teachers write their scientific works in the form of articles, the above goals will be maximally achieved. However, the counterproductive situation that is still observed today is that very few teachers submit their articles for publication in national journals or proceedings. It is because the lack of knowledge of how to publish their research work and writing skill, then the training for publication in needed for this gap. Therefore, intensive assistance needs to be done so that the gap can be covered. In this present paper, a description of the implementation of scientific article writing training for secondary school science and physics teachers is reported. The training was conducted online with participating teachers spread across various schools in Indonesia. The online training was held for three days and assistance in writing scientific articles for approximately one month, during the COVID-19 pandemic, until the participants succeeded in collecting the final product in the form of scientific articles.